Financial sector policy for developing countries : a reader - Caprio, Gerard; Honohan, Patrick; Vittas, Dimitri (Washington, DC : World Bank ; New York : Oxford University Press, 2002)
The book collects ten complementary essays on different aspects of financial sector policy for developing and transitional economies. The essays, by leading theoreticians and practioners in the field, draw on the history of financial sector policy reforms to derive lessons for the future.
Includes bibliographical references.
gau 20/06/14, rua 05/09/16
Loans
Keywords: Finance; Banks and banking; International finance; Developing countries